2017
DOI: 10.1515/cipms-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of gestational hypertension development

Abstract: The problem of gestational hypertension (GH) remains to be of current concern in obstetric practice. The purpose of this study, therefore, was to determine the risk factors for GH development. We examined 53 pregnant women and allocated them to 2 groups: the main group -pregnant women with gestational hypertension (n = 30) and the control group -pregnant women without the pathology (n = 23). The selection of persons for the study was carried out on the basis of detailed history taking, examination and complain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…In the present study, the prevalence of GH was 7.7%, and thus it was higher than that observed in other published studies 33 , 37 , 39 , 40 , yet lower than previously reported 32 , 35 , 38 and similar to that found by other scientists 42 . The results of our study are consistent with those of previous studies that demonstrated significant associations of maternal GH with advanced maternal age 43 , 44 , maternal obesity 44 , 45 , and cardiac diseases 46 . In our study, children born to women with GH had lower Apgar scores at 1 and 5 min and lower mean gestational age at birth, and in adolescence, they were heavier, more frequently had overweight/obesity, had a greater WHtR, and had higher BP levels than children of women without GH did.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the prevalence of GH was 7.7%, and thus it was higher than that observed in other published studies 33 , 37 , 39 , 40 , yet lower than previously reported 32 , 35 , 38 and similar to that found by other scientists 42 . The results of our study are consistent with those of previous studies that demonstrated significant associations of maternal GH with advanced maternal age 43 , 44 , maternal obesity 44 , 45 , and cardiac diseases 46 . In our study, children born to women with GH had lower Apgar scores at 1 and 5 min and lower mean gestational age at birth, and in adolescence, they were heavier, more frequently had overweight/obesity, had a greater WHtR, and had higher BP levels than children of women without GH did.…”
Section: Discussionsupporting
confidence: 93%
“…In this way, arterial hypertension has been demonstrated as one of the major contributors to developing a fatal clinical course of COVID-19 in the general population [6]; in the pregnant collective, where hypertensive disorders are frequent, one of the most prevalent disorders is gestational hypertension, which could constitute a substantial risk factor for COVID-19 disease [18]. Gestational hypertension on its own could be devastating, causing pre-eclampsia, which can lead to placental abruption, abortion, or even death of the mother due to multiple organ failure [19,20].…”
Section: Introductionmentioning
confidence: 99%